Penerapan Metode Total Physical Response Untuk Meningkatkan Keterampilan Berbicara Bahasa Arab di Madrasah Ibtidaiyah - Siffa Lutfatul Qolbi; Dadan F Ramdhan; Muhammad Sofyan (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study was motivated by the low Arabic speaking skills of Madrasah Ibtidaiyah students due to the use of monotonous teaching methods, which made students less active, hesitant, and lacking confidence in speaking. Therefore, this research aimed to improve students’ Arabic speaking skills through the implementation of the Total Physical Response (TPR) method. The study employed Classroom Action Research (CAR) conducted in two cycles, with data collected through oral performance tests to assess speaking skills, as well as observation and documentation to evaluate teacher and student activities. The results indicated significant improvement in students’ speaking skills across cycles. The average score in the pre-cycle was 54.09 with 31.82% mastery, increasing to 66.14 with 54.54% mastery in cycle I, and reaching 72.05 with 81.82% mastery in cycle II. The findings also showed that the TPR method enhanced students’ confidence, activeness, and ability to imitate vocabulary and sentence patterns with clearer pronunciation. In conclusion, the TPR method is effective in improving Arabic speaking skills among fifth-grade students at MIS Borosole.